2002
DOI: 10.1063/1.1436302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of P doping on the thermoelectric properties of β-FeSi2

Abstract: The effects of P substitution for Si as an n-type dopant on the thermoelectric properties of hot-pressed β-FeSi2 were investigated. The Seebeck coefficient, electrical resistivity, and thermal conductivity of the FeSi2−xPx were measured from room temperature to 1100 K, and then the power factor and figure of merit were evaluated. The Seebeck coefficient of the hot-pressed FeSi2−xPx was negative, indicating that P atoms were definitely substituted for Si atoms as an n-type dopant in the β phase. The samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…The E g values at high temperature range for intrinsic conductive region are 0.60 and 0.56 eV for Al-and Co-doped samples. Compared to the energy gap of non-doped ␤-FeSi 2 , 0.90 eV [11], the values of E g for Al-and Co-doped FeSi 2 are low. It was reported that the energy gap was reduced when a ptype dopant, such as Mn, Nb, or Zr, or a n-type dopant, such as P, was added in FeSi 2 , which expanded the width of the valence band [11].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The E g values at high temperature range for intrinsic conductive region are 0.60 and 0.56 eV for Al-and Co-doped samples. Compared to the energy gap of non-doped ␤-FeSi 2 , 0.90 eV [11], the values of E g for Al-and Co-doped FeSi 2 are low. It was reported that the energy gap was reduced when a ptype dopant, such as Mn, Nb, or Zr, or a n-type dopant, such as P, was added in FeSi 2 , which expanded the width of the valence band [11].…”
Section: Resultsmentioning
confidence: 79%
“…The main parameter required to improve for ␤-FeSi 2 is the ratio of electrical conductivity to thermal conductivity, if a high figure of merit is expected to achieve [5,7]. ␤-FeSi 2 is an intrinsic semiconductor, and some doping elements [4,[9][10][11][12] were added to form p-or n-type semiconductor to increase its electrical conductivity. The microstructural properties (grain size and porosity) of the material also have the influence on materials thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to improve the thermoelectric properties of p-type FeSi 2 have been made by doping with Mn, Al, Cr, and Zr [8][9][10][11]. Ito et al managed to obtain p-type FeSi 2 with high thermoelectric performance comparable to that of the conventional Fe 0.98 Co 0.02 Si 2 by doping FeSi 2 with phosphorus [12].…”
Section: Introductionmentioning
confidence: 98%
“…1,2) The performance of a thermoelectric material is generally evaluated by the dimensionless figure of merit, ZT, which is calculated from the Seebeck coefficient, S, electrical resistivity, , thermal conductivity, , and the absolute temperature, T, in the equation ZT ¼ S 2 T=. In order to improve the electrical properties of the -FeSi 2 , such as Seebeck coefficient and electrical resistivity, the doping of various elements, Co, [3][4][5][6][7][8][9] Cr, 8) Ni, 8,9) Mn, 8,[10][11][12] Al, 3,4,6,12) Cu, 13) B, 14) Nb, 15) Zr, 16) or P, 17) etc., has been attempted during sample preparation. Co and Mn are well known as good dopants for n-type and p-type -FeSi 2 materials, respectively.…”
Section: Introductionmentioning
confidence: 99%